Social Values in a Collection of Lukisan Kaligrafi by A. Mustofa Bisri and The Lessons Aplication at High School - Nur Zaman; Tato Nuryanto; Emah Khuzaemah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This study aims to describe the social values ​​contained in A. Mustofa Bisri's Calligraphy Painting Short Story Collection and describe their application in learning in high school. The method used in this research is descriptive qualitative method. The data source used in this research is the book Collection of Calligraphy Painting short stories by A. Mustofa Bisri which was published in 2009. The data was collected using documentation techniques. Data analysis was performed using an interactive analysis model. The results showed that: (1) there are several forms of social values ​​in the collection of calligraphy paintings by A. Mustofa Bisri, which are divided into three forms, including love, responsibility, and life harmony. (2) learning Calligraphy Painting short story collection has basic competence to identify the values ​​of life contained in the collection of short stories that are read. The methods used were group discussions, questions and answers, and assignments. Learning activities include preliminary activities, core activities, and closing activities.